Utilizing Building Information Modelling Technology To Modelling Abutment: Revit - Pratama, Sandhi Rio; Rifai, Andri Irfan; Pamadi, Mulia; Handayani, Susanty (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Building Information Modeling (BIM) has transformed the construction industry by offering a robust platform that integrates design, analysis, and construction processes within a single digital environment. This research explores the application of BIM technology, explicitly using Autodesk Revit, in modeling bridge abutments—an essential component in bridge construction that supports and distributes loads from the superstructure to the foundation. The study aims to demonstrate how BIM enhances the efficiency, accuracy, and sustainability of abutment design and construction. The methodology involves a comprehensive review of existing literature on BIM and bridge abutment design, focusing on technological advancements, case studies, and best practices. Additionally, practical implementation of BIM using Revit is conducted to develop detailed 3D models of abutments, incorporating architectural, structural, and geotechnical elements. The benefits of BIM in this context include improved collaboration among multidisciplinary teams, enhanced visualization capabilities for design optimization, and early detection of clashes and constructability issues. The research investigates the integration of Geographic Information Systems (GIS) with BIM to enhance site selection and environmental assessment phases, ensuring informed decision-making throughout the project lifecycle. Innovations in materials science, such as the use of fiber-reinforced polymers (FRP) and ultra-high-performance concrete (UHPC), are also considered for their potential to enhance the durability and longevity of bridge abutments. Ultimately, this study contributes to advancing the application of BIM in civil engineering, particularly in bridge construction, by showcasing Revit's capabilities in creating accurate, data-rich models that improve project outcomes.